Phosphorylation of the Pseudomonas effector AvrPtoB by Arabidopsis SnRK2.8 Is Required for Bacterial Virulence - Lei, Lei (Mol Plant, 2020)
A critical component controlling bacterial virulence is the delivery of pathogen effectors into plant cells during infection. Effectors alter host metabolism and immunity for the benefit of pathogens. Multiple effectors are phosphorylated by host kinases, and this posttranslational modification is important for their activity. We sought to identify host kinases involved in effector phosphorylation. Multiple phosphorylated effector residues matched the proposed consensus motif for the plant calcium-dependent protein kinase (CDPK) and Snf1-related kinase (SnRK) superfamily. The conserved Pseudomonas effector AvrPtoB acts as an E3 ubiquitin ligase and promotes bacterial virulence. In this study, we identified a member of the Arabidopsis SnRK family, SnRK2.8, which interacts with AvrPtoB in yeast and in planta. We showed that SnRK2.8 was required for AvrPtoB virulence functions, including facilitating bacterial colonization, suppression of callose deposition, and targeting the plant defense regulator NPR1 and flagellin receptor FLS2. Mass spectrometry analyses revealed that AvrPtoB phosphorylation occurs at multiple serine residues in planta, with S258 phosphorylation significantly reduced in the snrk2.8 knockout. AvrPtoB phospho-null mutants exhibited compromised virulence functions and were unable to suppress NPR1 accumulation, FLS2 accumulation, or inhibit FLS2-BAK1 complex formation upon flagellin perception. Taken together, these data identify a conserved plant kinase utilized by a pathogen effector to promote disease.